Acute hyperammonemic encephalopathy masquerading as postoperative delirium in a patient who underwent lung surgery: a case report - Chao-Qin Chen; Zhen-Ping Hu; Xu-Jie Ma; Xiao-Dong Tang; Xia Zheng; Yong-Xing Yao (BMC Anesthesiology)
Abstract Background Acute hyperammonemic encephalopathy (AHE) is a life-threatening condition. Hyperammonemia-induced mental disorders that appear after surgery and general anesthesia can be easily confused with postoperative delirium, especially in patients without signs of liver dysfunction. Currently, no reports of AHE precipitated by operative stress or general anesthesia exists. Here, we describe a patient without obvious liver dysfunction who developed AHE after general anesthesia and was diagnosed with postoperative delirium. Gene sequencing revealed that the patient had ornithine transcarbamylase deficiency (OTCD), which led to AHE and hepatic coma. Case presentation A 41-year-old man with a history of mild hypertension and depression was scheduled to undergo lung wedge resection under general anesthesia. Laboratory examination revealed low blood urea nitrogen levels. The anesthesia and surgery were uneventful. Four hours after returning to the surgical ward, the patient experienced agitation and developed mental disorders. His Confusion Assessment Method score was positive, and the Nursing Delirium Screening Scale score was 6; therefore, he was medically treated for postoperative delirium. However, his symptoms did not improve over the following days. On the 3rd postoperative day, the patient became unconscious and experienced limb twitching. Blood analysis revealed severe hyperammonemia (498 µmol/L) and respiratory alkalosis. Consequently, the patient underwent tracheal intubation and continuous venovenous hemodiafiltration, along with comprehensive supportive treatments, including intracranial pressure reduction and antiviral and gamma globulin therapy. However, the patient’s serum ammonia level remained high. A computed tomography scan of the head revealed diffuse cerebral swelling. On the ninth postoperative day, the patient remained in a deep coma, with loss of brainstem reflex and brain electrical activity, at which point the treatment was terminated by family members. Postmortem genetic sequences revealed that the patient had OTCD. Conclusions AHE following general anesthesia with no evidence of liver failure can be easily misdiagnosed because of its non-characteristic clinical features. We recommend that in patients who experience refractory mental disorders after surgery, clinicians should remain vigilant for signs of hyperammonemia.